Supramolecular assembly and spectroscopic characterization of indolenine–barbituric acid zwitterions - Ramle, Abdul Qaiyum; Tiekink, Edward R. T. *; Fei, Chee Chin; Julkapli, Nurhidayatullaili Muhd; Basirun, Wan Jefrey (Royal Society of Chemistry, 2021)
A series of indolenine and barbituric acid zwitterion scaffolds were synthesized with a maximum yield of 98% via the formation of C–C single bond. The structures were unambiguously elucidated by various spectroscopic techniques such as 1H, 13C NMR (1D, 2D), FT-IR and high-resolution mass spectrometry (HRMS). Single crystal X-ray crystallography analysis on 22, as the 22.DMF 1:1 solvate, confirms the presence of wellseparated iminium and enolate centres, and also confirms that the BA ring is highly twisted with respect to the indolenine ring due to steric hindrance. The presence of N–H∙∙∙O and N–H∙∙∙O- groups favour a 1D-supramolecular assembly in the solid-state. The orange or yellow solutions of the zwitterion exhibit an intense molar absorption coefficient, ε ranging between 0.21 × 104 and 2.93 × 104 M-1 cm-1 in the UV-vis region. Furthermore, the Intramolecular Charge Transfer (ICT) peak of zwitterion displays a hypsochromic shift in absorption behavior when the polarity of the solvent increases. Moreover, treatment of small amount of trifluoroacetic acid (TFA) to the DMF solution of 19 resulted in the protonation of an enolate of BA ring. This fundamental work provides valuable structural design and information for the construction of supramolecular chemistry and synthetic dyes based on indolenine substituted BA derivatives.